Intrathymic Notch3 and CXCR4 combinatorial interplay facilitates T-cell leukemia propagation. Issue 49 (6th December 2018) - Ferrandino, Francesca; Bernardini, Giovanni; Tsaouli, Georgia; Grazioli, Paola; Campese, Antonio; Noce, Claudia; Ciuffetta, Ambra; Vacca, Alessandra; Besharat, Zein; Bellavia, Diana; Screpanti, Isabella; Felli, Maria
Abstract Notch hyperactivation dominates T-cell acute lymphoblastic leukemia development, but the mechanisms underlying "pre-leukemic" cell dissemination are still unclear. Here we describe how deregulated Notch3 signaling enhances CXCR4 cell-surface expression and migratory ability of CD4+ CD8+ thymocytes, possibly contributing to "pre-leukemic" cell propagation, early in disease progression. In transgenic mice overexpressing the constitutively active Notch3 intracellular domain, we detect the progressive increase in circulating blood and bone marrow of CD4+ CD8+ cells, characterized by high and combined surface expression of Notch3 and CXCR4. We report for the first time that transplantation of such CD4+ CD8+ cells reveals their competence in infiltrating spleen and bone marrow of immunocompromised recipient mice. We also show that CXCR4 surface expression is central to the migratory ability of CD4+ CD8+ cells and such an expression is regulated by Notch3 through β-arrestin in human leukemia cells. De novo, we propose that hyperactive Notch3 signaling by boosting CXCR4-dependent migration promotes anomalous egression of CD4+ CD8+ cells from the thymus in early leukemia stages. In fact, in vivo CXCR4 antagonism prevents bone marrow colonization by such CD4+ CD8+ cells in young Notch3 transgenic mice. Therefore, our data suggest that combined therapies precociously counteracting intrathymic Notch3/CXCR4 crosstalk may prevent dissemination of "pre-leukemic" CD4+ CD8+ cells, by a "thymus-autonomous" mechanism.